Do Instagram Profiles Accurately Portray Personality? An Investigation Into Idealized Online Self-Presentation - Harris, Elspbeth; Bardey, Aurore C. (Frontiers in Psychology, 2019)
Instagram users are consistently exposed to the presentation of idealized selves. Although studies have examined online self-presentation in general, little attention has been paid to self-presentation in a visual online setting, such as Instagram. The present investigation examined the extent to which Instagram account holders engage in idealized online self-presentation through a mixed-methods approach. Quantitative results (Study 1) showed a difference between how the observers perceived the Instagram account holders’ personality and the Instagram account holders’ personality self-reports. Qualitative findings (Study 2) revealed four major themes: 1) Selfies as a personality predictor; 2) Faces as a personality predictor; 3) Layout as personality predictor, 4) Misuse of social networks and its consequence for communication. Our results also indicated that the halo effect is integral to the online self-presentational process, suggesting that an aesthetically pleasing Instagram account or account holder will be better received and thought as having particularly positive personality traits.